Pengaruh Pupuk Hayati Mikoriza Terhadap Pertumbuhan dan Hasil Tanaman Tomat (Solanum lycopersicum) dengan Rancangan Acak Lengkap - Septia Cahaya Sari Sipayung; Thanaya Lovry Lastiar; Trinita Melyana Hutagalung; Widya Narti Lubis; Putri Maulidina Fadilah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This study aims to analyze the effect of mycorrhizal biofertilizer on the growth of tomato plants (Solanum lycopersicum) height over a period of 8 weeks. A Completely Randomized Design (CRD) was employed with six treatments: no mycorrhiza (Mo), low doses (M0.1), and high doses (M1, M1.1, M2, M2.1) with variations of 5 grams and 10 grams. The results showed that the application of mycorrhiza at higher doses resulted in significant growth compared to the control treatment. By week 8, plants receiving treatments M2 and M2.1 reached an average height of 32 cm and 32.5 cm, while the control treatment without mycorrhiza only reached 9 cm. Variance analysis (ANOVA) indicated significant differences at the 95% confidence level among treatments. Therefore, the use of mycorrhizal biofertilizer has been proven effective in enhancing the height growth of tomato plants, which is expected to increase productivity in horticultural cultivation.